2015
DOI: 10.14712/18059694.2015.98
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neck infections of Odontogenic Origin and Their Clinical Significance. A Retrospective Study from Hradec Králové, Czech Republic

Abstract: Summary:Introduction: Cellulitis remains a very serious disease even today. Mortality, which varied between 10-40%, has been reduced owing to the standard securing of airway patency and use of an appropriate surgical treatment approach. Materials and methods: A total of 195 patients were hospitalised for cellulitis at the University Hospital in Hradec Králové during 2007-2011. The following parameters were evaluated: age, gender, dependence of incidence of the disease on the season of the year, frequency of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…According to various studies, 20% to 70% of DNI patients received surgical drainage for deep neck abscess . In our study, 26.4% of patients with RA‐DNI patients and 29.9% of patients with non–RA‐DNI received surgical drainage.…”
Section: Discussionsupporting
confidence: 47%
“…According to various studies, 20% to 70% of DNI patients received surgical drainage for deep neck abscess . In our study, 26.4% of patients with RA‐DNI patients and 29.9% of patients with non–RA‐DNI received surgical drainage.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies have reported that surgical treatment was used in 55–80% of patients with DNI [ 4 , 9 , 24 , 25 , 26 , 27 , 28 ]. In our study, few patients received surgical treatment in both the cohorts (T1DM: 33.3% and non-DM: 18.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, few patients received surgical treatment in both the cohorts (T1DM: 33.3% and non-DM: 18.7%). This difference in percentage may result from previous studies being conducted in medical centers or tertiary hospitals, which receive and treat patients with severe DNI [ 4 , 8 , 9 , 24 , 25 , 26 , 27 ]. Hence, patients with severe DNI were more likely accept surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…By means of seasonal dominancy, it was observed that trimodal peaks were spread throughout the year. A recent review on the issue by Doležalová et al [5] reported a trimodal peak according to seasons. Therefore we concluded that deep neck infections can be observed throughout the year.…”
Section: Discussionmentioning
confidence: 99%